We are the voice of change: educação bilíngue no Ensino Fundamental I visando à formação de cidadãos globais - Macedo, Luiza Cristiane Ribeiro dos Santos (Universidade do Vale do Rio dos Sinos, 2022)
This research aims to create, implant and evaluate collectively, a bilingual and integrated lesson planning for the 4th grade of Elementary School at Medianeira School also based on CLIL approach and underpinned on integral formation outlooking global citizenship formation. Medianeira School is located in Curitiba City and is one of the schools integrated to Rede Jesuíta de Educação (Jesuit Educational Network). Since 2019 Medianeira School has been implementing a bilingual education project from the Kindergarten to the 9th grade of Elementary School. This work sought produce relevant knowledge for teachers’ formation and teaching praxis in bilingual education and education for global citizenship which are in development at the institution. The methodology used was qualitative approach, and for the methodological procedure it was chosen research-action. For this purpose, this research was applied with a group of seven teachers from the 4th grade of Elementary School, therefore four were general teachers and three were teachers of the special classes English, Physical Education and Art. It was necessary seven meetings with the teachers’ group for creating a bilingual integrated lesson planning, which was organized for being executed for two weeks of classes. The topic explored on this lesson planning was focused on developing consciousness about environmental preservation and enlarge clarification of historical facts related to the unbridled environment devastation during the colonial period in Paraná State. The theoretical foundation of this research is based on implementation of bilingual education according to CLIL approach, education for global citizenship, democratic school management and evaluative learning process. The data collection leaded to a narrative analysis about the process of cocreating and execution of this bilingual integrated lesson planning which resulted in reflections and recommendations for teaching praxis improvement. The investigation indicated viability of an interdisciplinary teaching-working through a collaborative creation of a lesson planning that promotes English language learning as a way to acquire knowledge from other areas and that seeks global citizenship formation.
Keywords: Educação para a cidadania global; Educação bilíngue; Abordagem CLIL; Integração curricular; Gestão educacional; Education for global citizenship; Bilingual education; CLIL approach; Curricular integration; Educational management; ACCNPQ::Ciências Humanas::Educação